Short-Run Pain, Long-Run Gain : The Effects of Financial Liberalization - Kaminsky, Graciela Laura; Schmukler, Sergio L. (World Bank, Washington, DC, 2014)
The authors examine the short- and long-run effects of financial liberalization on capital markets. To do so, they construct a new comprehensive chronology of financial liberalization in 28 developed and emerging economies since 1973. The authors also construct an algorithm to identify booms and busts in stock market prices. The results indicate that financial liberalization is followed by more pronounced boom-bust cycles in the short run. But financial liberalization leads to more stable markets in the long run. Finally, the authors analyze the sequencing of liberalization and institutional reforms to understand the contrasting short- and long-run effects of liberalization.